2020
DOI: 10.3390/app10207237
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost Goethite Nanorods for As (III) and Se (VI) Removal from Water

Abstract: Arsenite (As(III)) and Selenate (Se(VI)) are universally touted as extremely toxic oxyanions in natural and industrial water systems. Thus, the production of low-cost adsorbents that are scalable and toxic-free is of great importance today. In this work, a large-scale goethite nanorods (α-FeOOH NRs) is synthesized using a modified rapid hydrolysis method. The obtained powder is characterized using different multidisciplinary techniques. Accordingly, the results showed uniform and straight nanorods (length ~400… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…The last step changes at about 375 °C are due to the transformation of magnetite to hematite and maghemite, respectively. All three weight loss stages are in consistency with the results reported in the literature. The total weight loss for goethite and lepidocrocite was 13.3 and 11.3%, respectively. Comparison of weight loss values in each stage indicates that the most difference in weight losses of two adsorbents belongs to the dehydroxylation step, which suggests that goethite includes approximately 20% more hydroxyl groups than lepidocrocite.…”
Section: Results and Discussionsupporting
confidence: 88%
“…The last step changes at about 375 °C are due to the transformation of magnetite to hematite and maghemite, respectively. All three weight loss stages are in consistency with the results reported in the literature. The total weight loss for goethite and lepidocrocite was 13.3 and 11.3%, respectively. Comparison of weight loss values in each stage indicates that the most difference in weight losses of two adsorbents belongs to the dehydroxylation step, which suggests that goethite includes approximately 20% more hydroxyl groups than lepidocrocite.…”
Section: Results and Discussionsupporting
confidence: 88%
“…27 Goethite also been used to remove impurities such as heavy metals from water. 28 More or similarly, here also the intensity of the peaks has been increased from 3000 cps to 7000 cps when the clay was treated with temperature. When cationic modification was done to Deniyaya raw clay intensity of peaks has been vastly decreased and only the peak relevant to quartz was prominent.…”
Section: Ftir Analysismentioning
confidence: 62%
“…Since the vibrational bands between 1800 and 1000 cm −1 generally belong to water bending modes, the bands observed at ~1650 cm −1 can be assigned to the bending vibration of weakly adsorbed molecular water [47]. However, it was suggested that the peak at ~1390 cm −1 corresponds to the structural hydroxyl groups at the surface of goethite [48]. The ATR-FTIR spectrum also shows the strong stretching vibration band at approximately 3129 cm -1 [49] that can be attributed to bulk hydroxyls.…”
Section: Transformation Of Iron Precipitates Under Alkaline Conditionsmentioning
confidence: 99%